(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2008)
This document contains the report of the Expert Consultation on International Guidelines for the Management of Deep-sea Fisheries in the High Seas held in Bangkok, Thailand, from 11 to 14 September 2007. The Expert Consultation was convened to review an initial draft of the International Guidelines as called for by the FAO Committee on Fisheries at its twentyseventh session in 2007. This expert consultation was preceded by an expert consultation in November 2006 in Bangkok, Thailand, on deep-sea fisheries in the high seas. The consultation adopted a draft of the international guidelines to be forwarded on to a technical consultation for review and adoption.
Keywords: Deep-sea fisheries,Fisheries management,Quản lý nghề cá,Cá vùng biển sâu